A greeting of the spirit : selected poetry of John Keats with commentaries - Keats, John, 1795-1821 (The Belknap Press of Harvard University Press, 2022)
"A renowned Keats scholar illuminates the poet's extraordinary career, in a new edition featuring eighty-five verse selections with commentary. A Greeting of the Spirit greets everyone at every level of expertise who is interested in this extraordinary poetry of John Keats, interested in extraordinary imagination, interested in reading with care: adventurous undergraduates, graduate students, professional peers, and with its lucidity of style and access, anyone open to a spirited engagement with remarkable, phenomenal poetry"--